Bugs as drugs: The role of microbiome in cancer focusing on immunotherapeutics. (January 2021) - Araujo, Daniel V.; Watson, Geoffrey A.; Oliva, Marc; Heirali, Alya; Coburn, Bryan; Spreafico, Anna; Siu, Lillian L.
Highlights: The human microbiome consisting of microorganisms living on and in the human body, their collective genomes and metabolic products has been implicated in many disease processes including cancer. An emerging body of literature suggests an important role for the gut microbiome in modulating response to immune checkpoint blockade across different cancer types. Microbiome composition should be measured, analyzed and reported using standard techniques and methodology. There are multiple interventional strategies that can be used to modify the microbiome, including diet, prebiotics, probiotics, fecal microbiota transplantation, microbial consortia and stool substitutes, and antibiotics to sterilize selected taxa. Proof-of-principle and proof-of-concept clinical trials with appropriate controls are needed to demonstrate safety, efficacy and clinical utility of human microbiome modulation in cancer. Abstract: The human microbiome comprising microorganisms, their collective genomes and metabolic products has gained tremendous research interest in oncology, as multiple cohorts and case studies have demonstrated discernible interpatient differences in this ecosystem based on clinical variables including disease type, stage, diet, antibiotic usage, cancer treatments, therapeutic responses and toxicities. The modulation of the gut microbiome is the subject of many ongoing preclinical and clinical investigations, through the manipulation of diet, as well as the use of prebiotics, probiotics, specific antibiotics, fecal microbial transplantation, microbial consortia and stool substitutes. Standardization and quality control are needed to maximize the information being generated in this growing field, ranging from technical assays to measure microbiome composition, to methodological aspects in the analysis and reporting of results. Proof-of-mechanism and proof-of-concept clinical trials with appropriate controls are needed to confirm or refute the feasibility, safety and ultimately the clinical utility of human microbiome modulation in cancer patients.